Numerical Simulation Andmodelingofunsteady Flowaround Anairfoil. (aerodynamic Form) - Habib, M. Y.; Djaaffar, R. (University of Eloued جامعة الوادي, 2014)
Duringthis work, we simulatedanunsteady flowaround anairfoiltypeNACA0012using theFluent software. The objectiveis to controlthe codeon the one handandon the other handthe simulationofunsteady flows. By simulatinganunsteady flowReynolds number(Re =6.85*106) andMach number(M =0.3), we havethe flowingwitha grid(mesh) adequatenumerical resultsandexperimental dataare ingood agreement. To representthe results ofthe simulationwe havevalidated bycomparing the valuesof aerodynamic coefficientswith those ofexperimental data.
Articale in Journal of fundamental and Applied Sciences Vol. 06 N. 01
Keywords: Unsteady flow; Fluent;a singleequationmodel;NACA0012.